Modulating the expression of survivin and other basal epidermal proteins protects human skin from UVB damage and oxidative stress. (14th July 2015) - Labarrade, Florian; Bergeron, Laurine; Serre, Catherine; Lebleu, Alexia; Busuttil, Valère; Botto, Jean‐Marie; Domloge, Nouha
Summary Background The chromosomal passenger complex (CPC) is an assembly made of four interacting proteins: survivin, borealin, INCENP, and aurora kinase B. CPC is the key regulatory complex responsible for the correct development of cellular mitosis, accompanying each step of the chromosomal segregation. This control of mitosis is particularly important in undifferentiated cells that must renew themselves and also further differentiate and specialize. The epidermis is a self‐renewing tissue that needs to continuously generate new cells through proliferation and differentiation of progenitor cells. Both the mitosis supervision by the CPC and a correct extracellular environment are physiologically required for the homeostasis of the adult keratinocyte stem cells (KSCs) of the epidermis. KSCs are mainly found in the basal layer of the epidermis and are responsible for the replenishment and maintenance of the tissue, by compensating for the loss of terminally differentiated cells called corneocytes, especially during aging. Aim The aim of our study was to investigate the implication of survivin in epidermal renewal and the relationships between survivin expression and UVB‐induced DNA damage levels in cultured human keratinocytes and in skin biopsies. In parallel, the effects of a treatment by compound IV08.009 were studied. Material and methods Cultured human keratinocytes and skin biopsies were used in this study. KSCs‐enriched fractions of keratinocytes were isolated from total keratinocytes by differential attachment to a type IV collagen matrix. Survivin expression levels were assessed by immunoblotting in cultured keratinocytes, and α6‐integrin, β1‐integrin, keratin 15, and survivin were observed after immunodetection in skin biopsies cross sections. Comet assay, immunodetection of CPDs and of cleaved‐caspase 3, and electron microscopy were used to characterize UVB‐induced DNA damage. Results We demonstrated the ability of compound IV08.009 to efficiently protect ex vivo skin against basal UVB‐induced damage. Moreover, comet assay studies demonstrated the efficacy of IV08.009 in protecting DNA damage from UVB stress. We found that IV08.009 protects skin from apoptosis induced by oxidative stress, ex vivo. Electron microscopy confirmed the protective efficiency of IV08.009 on cell ultrastructural damage induced by UVB exposure. Conclusion Compound IV08.009 demonstrated to be effective in regulating survivin expression and in preserving the basal epidermis from stresses such as UVB and H2O2. These results suggest a protective activity of IV08.009 on the essential renewing potential of KSCs.